Topical administration of deep sea shark liver oil (DESSLO™) inhibit Nuclear Factor-kappa Beta (NF-κB) expression in Wistar rats (Rattus Norvegicus) skin exposed to ultraviolet-B - Devita Horax; A. A. G. P. Wiraguna; Gde Ngurah Indraguna Pinatih (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Introduction: Repeated exposure of the skin to UV-B rays induce reactive oxygen species (ROS) formation that activates Nuclear Factor-kappa Beta (NF-κB) and stimulates pro- inflammatory cytokines expression which leads to premature aging of skin. Deep-sea shark liver oil contains ±80% squalene which could help neutralized ROS. Therefore, the purpose of this study was to assess the effect of topical deep sea shark liver oil toward NF-κB expression in UV-B-exposed on wistar rat (Rattus norvegicus) skin. Methods: A true experimental posttest-only control study was conducted using 36 Wistar rats which divided into 2 groups (n= 18). Control group was exposed to UV-B and treated with topical placebo basis of glycerin while the treatment group was treated with topical deep sea shark liver oil. A total of 840 mJ/cm2 UV-B exposure was given for 4 weeks. NF-κB expression was examined by immunohistochemistry. Results: The mean NF-κB expression was significantly higher in control group at 30.8±3.81 while the treatment group treated with topical deep sea shark liver oil has average expression at 10.4±1.98. The independent t-test showed a t-value of 20.090, and a p-value of 0.033. Conclusion: It can be concluded that topical deep sea shark liver oil inhibits the expression of NF-κB expression in UV-B-exposed Wistar rat (Rattus norvegicus) skin.